Formulating the Philippine Services Strategy for Inclusive Growth - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2014)
The paper looks at the role of services in the economy and discusses why competitive services are necessary for achieving inclusive growth. An overview of Philippine services sectors is first presented highlighting their economic contribution as well as performance. This is followed by a discussion of the country's record in services trade particularly in exports. It suggests that a comprehensive and high profile services export initiative is needed to establish the Philippines as the heart of services trade in the Asia-Pacific region. Restrictions on the supply of services are then examined to have a better understanding of the general environment under which services are provided.Because regulatory and nonregulatory measures undermine the efficient supply of services, it is recommended that a trade-related audit of the laws and regulations affecting services be conducted with the view of removing those laws and regulations whose policy objective is no longer relevant or could be achieved by a less restrictive measure. In addition to improving the trade and investment environment, other policy areas are also important and these are suggested in the concluding section which presents the elements of a strategic framework to harness services for inclusive growth.
Keywords: 330; services sector; Philippines; services trade; inclusive growth; services